Investigation of Heat Transfer Enhancement and Flow Phenomena of Gas Turbine Blade Internal Cooling Passage - (:unkn) unknown (My University, 2022)
The turbomachinery industry is constantly struggling to improve gas turbine efficiency. The efficiency of a gas turbine depends on the turbine inlet temperature. Currently, the turbine inlet temperature can be as high as 1600°C. The turbine blade material is not able to withstand high temperatures. Efficient cooling can increase the durability and performance of the blade. Over the years, researchers have investigated different cooling methods such as rib turbulated cooling, dimple cooling, pin fin cooling, and jet impingement cooling. Rib cooling is applicable for the serpentine mid-section of the blade cooling channel. It was used for a long time as it shows better heat transfer enhancement compared to a smooth surface. The drawback of using a ribbed surface is excessive pressure drop which affects the thermal performance negatively. Dimple and pin-fin cooling are used for trailing edge cooling. The leading edge of the blade is cooled using the jet impingement method, where the rotor blade experiences the highest heat. Intense air-jet strikes at the target surface to heat transfer. This study investigated the heat transfer and airflow behavior of dimpled, rib-turbulated, pin-finned cooling channels and the application of guide vane with the dimpled cooling passages both experimentally and numerically.The investigation was conducted with a baseline case of a smooth surface cooling channel. The dimpled surface cooling channel was studied for partial spherical dimples. Three different dimple depths to diameter ratios i.e., 0.10, 0.25, and 0.50 were considered with one column of dimple in each leg. Later, the study moved to 2 column dimples with a 0.50 dimple depth to diameter ratio to obtain the maximum thermal efficiency. A newly designed dimple–leaf dimple was introduced in this investigation. The investigation showed that leaf dimples are more efficient compared to conventional partial spherical dimples. The research was also conducted to find out the best rib design. The ribbed surface was studied based on two different rib designs i.e., 30° ribs and 45° ribs. In addition, the current study investigated the effect of pin-fin on the cooling surface with two different designs of pin-fins i.e., partial spherical pin–fins and dome- shaped pin-fins. The study has been conducted both computationally and experimentally for stationary and rotational cases. The dome-shaped pin-finned channel exhibits better thermal performance based on the heat transfer and pressure drop effect. U and curve guide vanes were inserted at the bend region of the partial spherical dimpled cooling channel using different orientations i.e., depression and protrusion.
Keywords: Computational Fluid Dynamics; Dimple Ribs Pin-fins Guide Vane; Flow Behaviour; Gas Turbine; Heat Transfer Enhancement; Thermal Performance